التحديات القانونية للخطر السيبراني على المعاملات التجارية - Alaa Hussein Ali; Wurood Khalid Mohameed; Mahmood Shaker Alaloosh (Universiti Sains Islam Malaysia, 2025)
Malaysian Journal of Syariah and Law, 13(2), 456–475